2009
DOI: 10.1007/s11207-009-9383-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of STEREO/EUVI Loops with Potential Magnetic Field Models

Abstract: The Solar Terrestrial Relations Observatory (STEREO) provides the first opportunity to triangulate the three-dimensional coordinates of active region loops simultaneously from two different vantage points in space. Three-dimensional coordinates of the coronal magnetic field have been calculated with theoretical magnetic field models for decades, but it is only with the recent availability of STEREO data that a rigorous, quantitative comparison between observed loop geometries and theoretical magnetic field mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 16 publications
0
51
0
Order By: Relevance
“…We note that the validity of the potential approximation is questionable. For instance, Sandman et al (2009) and Aschwanden & Sandman (2010) found considerable misalignment between the magnetic field obtained from the potential approximation in comparison to the shapes of the coronal loops derived from the STEREO/EUVI observations (Wülser et al 2004). However, López Fuentes et al (2006) showed that linear force-free fields can also be quite poor approximations of the real magnetic field in active regions.…”
Section: Magnetic Field Extrapolationmentioning
confidence: 97%
“…We note that the validity of the potential approximation is questionable. For instance, Sandman et al (2009) and Aschwanden & Sandman (2010) found considerable misalignment between the magnetic field obtained from the potential approximation in comparison to the shapes of the coronal loops derived from the STEREO/EUVI observations (Wülser et al 2004). However, López Fuentes et al (2006) showed that linear force-free fields can also be quite poor approximations of the real magnetic field in active regions.…”
Section: Magnetic Field Extrapolationmentioning
confidence: 97%
“…The magnetic field in the environment of the oscillating loop can be modeled with potential-field or non-potential field models, but both are known to show misalignments with the 3D geometry of stereoscopically triangulated loops of the order of α mis ≈ 20 • − 40 • Sandman et al 2009), while simple potential field models calculated from a small set of unipolar magnetic charges (Aschwanden and Sandman 2010) or magnetic dipoles (Sandman and Aschwanden 2010) achieved a reduced misalignment of α mis = 13 • − 20 • . For a simple plausibility test of the magnetic field strength inferred from coronal seismology, we model the 3D field at the location of the oscillating loop with an analytical model of two unipolar charges with opposite magnetic polarities that are buried in depths z 1 and z 2 and have maximum longitudinal magnetic field strengths of B 1 = +187 G and B 2 = −63 G at the observed positions (x 1 , y 1 ) and (x 2 , y 2 ) of the nearest magnetic pores in the HMI magnetogram (marked with circles in Fig.…”
Section: Magnetic Field Modelingmentioning
confidence: 99%
“…Based on a study of three active regions modeled with potential field source surface (PFSS) magnetic fields, Sandman et al (2009) found misalignments of approximately 20 -40 degrees between the observed and modeled field structure. DeRosa et al (2009) modeled one of the three active regions with several different non-linear force-free field (NLFFF) models, using observations from Hinode's Solar Optical Telescope (SOT) in a restricted field of view.…”
Section: Introductionmentioning
confidence: 99%